Redox Imaging Using Cardiac Myocyte-Specific Transgenic Biosensor Mice. Issue 9 (14th October 2016) - Swain, Lija; Kesemeyer, Andrea; Meyer-Roxlau, Stefanie; Vettel, Christiane; Zieseniss, Anke; Güntsch, Annemarie; Jatho, Aline; Becker, Andreas; Nanadikar, Maithily S.; Morgan, Bruce; Dennerlein, Sven; Shah, Ajay M.; et al.
Abstract : Rationale: : Changes in redox potentials of cardiac myocytes are linked to several cardiovascular diseases. Redox alterations are currently mostly described qualitatively using chemical sensors, which however do not allow quantifying redox potentials, lack specificity, and the possibility to analyze subcellular domains. Recent advances to quantitatively describe defined redox changes include the application of genetically encoded redox biosensors. Objective: : Establishment of mouse models, which allow the quantification of the glutathione redox potential ( E GSH ) in the cytoplasm and the mitochondrial matrix of isolated cardiac myocytes and in Langendorff-perfused hearts based on the use of the redox-sensitive green fluorescent protein 2, coupled to the glutaredoxin 1 (Grx1-roGFP2). Methods and Results: : We generated transgenic mice with cardiac myocyte–restricted expression of Grx1-roGFP2 targeted either to the mitochondrial matrix or to the cytoplasm. The response of the roGFP2 toward H2 O2, diamide, and dithiothreitol was titrated and used to determine the E GSH in isolated cardiac myocytes and in Langendorff-perfused hearts. Distinct E GSH were observed in the cytoplasm and the mitochondrial matrix. Stimulation of the cardiac myocytes with isoprenaline, angiotensin II, or exposure to hypoxia/reoxygenation additionally underscored that these compartments responded independently. A compartment-specific response was also observed 3 to 14 days after myocardial infarction. Conclusions: : We introduce redox biosensor mice as a new tool, which allows quantification of defined alterations of E GSH in the cytoplasm and the mitochondrial matrix in cardiac myocytes and can be exploited to answer questions in basic and translational cardiovascular research. Abstract : Supplemental Digital Content is available in the text.